An Atomic Force Microscopy study of the growth of calcite in the presence of sodium sulfate - Vavouraki, A.; Putnis, Christine; Putnis, Andrew; Koutsoukos, P. (Elsevier Science BV, 2008)
In situ atomic force microscopy (AFM) has been used to compare the growth of pure calcite and the growth of calcite in the presence of sulfate ions from aqueous solutions at a constant value of supersaturation (S.I. = 0.89) with respect to calcite. The effect of sulfate ions on calcite growth rates is determined and a potential incorporation of sulfate ions is identified in the calcite during growth. Solutions supersaturated with respect to calcite with solution concentration ratio of one and a constant pH of 10.2, were prepared and sulfate was added as Na2SO4 aqueous solution. The solution composition was readjusted in order to keep the supersaturation and pH constant. PHREEQC was used to determine relevant solution concentrations. In situ AFM experiments of calcite growth were performed using a fluid cell and flowing solutions passed over a freshly cleaved calcite surface. Growth rates were determined from the closure of the rhombohedral etch pits induced by initial dissolution with pure water. The spreading rate of 2-dimensional nuclei was also measured. At low concentrations of sulfate (= 0.5 mM), no effect on the growth rate of the calcite was observed. At higher concentrations (2 to 3 mM) of sulfate, the growth rate increased, possibly because a higher concentration of calcium and carbonate was necessary to maintain the supersaturation constant. At much higher concentrations of additional sulfate (up to 60 mM) the growth rate of the calcite was substantially decreased, despite the fact that a further increase of calcium and carbonate was required. The morphology of 2-dimensional growth nuclei became increasingly elongated with increasing sulfate content. Measurements of step height showed that newly grown steps were approximately 1 Å higher when grown in high sulfate concentrations, compared to steps grown in sulfate-free solutions. At sulfate concentrations above 5 mM the growth mechanism changes from layer growth to surface roughening. These observations suggest that the new growth has incorporated sulfate into the calcite surface. © 2008 Elsevier B.V. All rights reserved.